REFORMASI BUDAYA BIROKRASI DALAM MEWUJUDKAN PEMERINTAHAN YANG AKUNTABEL, TRANSPARAN, DAN BERORIENTASI KEPADA PELAYANAN PUBLIK1 - Taufiq Effendi2 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2005)
If vigilantly observed, the portrait of Indonesian bureaucracy illustrates a pile ofcritical problems. The problems in the bureaucratic area do not merely compriseregulatory matters such as the cases of annulled regulations. They also include other aspects such as malpractice in the budget spending, unprofessional manner in service delivery, and low and unmeasured performance accountability. All these are against the fact that bureaucracy should function to serve the society. With such a condition, efforts to provide quality service and to create prosperous society within the country have proved to be merely a utopia. Therefore, a strategic bureaucratic reform needs to be revolved in a consistent and under-controlled way. It is obvious that improving public service through bureaucratic reform and corporateculture is not easy and time-consuming. For this purpose, it needs a strongcommitment among government apparatus both central and local, morality fromgovernment apparatus both personal and professional, appropriate public policy, andthe optimal implementation of managerial functions.